Pengaruh Treatment Aerasi dan Ukuran Bijih terhadap Persen Ekstraksi Emas dengan Metode Agitation Leach Test - Arief, Arief Rakhman Hakim; Wahyuningsih, Tri; Ravi'i; Yanas, Yogi Gautama; Usman, Fahrul Rozzi (LPPM ITK, 2023)
Generally, gold processing in the world is carried out through a leaching process to extract its gold content. One of the techniques commonly used in melindi gold ore, especially those with low grades, is the heap leaching method. One of the companies that manages gold with this technique is PT J Resources Bolaang Mongondow. In the heap leaching process at PT J Resources Bolaang Mongondow, there are several parameters that determine the final result of this process, including the concentration of dissolved oxygen and the size of the ore. This study aims to see the effect of aeration and ore size on percent gold extraction through the principle of leaching with the agitation leach test. This study used gold oxide ores with sizes of +6 and -6 mm. The two measures were each subjected to aeration and non-aeration treatment in the leaching process for 48 hours. From the results of experiments that have been carried out, it was found that the highest percent of extraction was produced at a size of +6 mm with a non-aeration treatment of 90%. While at a size of -6 mm, the highest percentage of extraction was obtained in aeration treatment of 84%. After data analysis, it was found that these results are highly dependent on oxygen levels and base metal content in the leaching process.